Prevalence of frailty among rural community-dwelling elderly: a cross-sectional study in central India - S. R., Shilpa; Lanjewar, Shilpa; Narlawar, Uday W.; P., Thungamithirai; U. I., Akash Gopi; P., Ajaya Krishnan (International Journal Of Community Medicine And Public Health, 2024)
Background: People around the world are experiencing increased longevity. Top of Form Bottom of Form As the structure of the population changes, so do the health challenges we encounter, which means medical care also has to adapt accordingly. With the increase in the proportion of elderly, there is a corresponding increase in the prevalence of frailty. Information on the prevalence of frailty in the rural areas of India is scarce, where the health of the elderly is often neglected. The objective of this study is to evaluate the prevalence of frailty within a rural region of Maharashtra. Methods: A community-based cross-sectional study was conducted on 114 elderly adults residing in a rural area in central India. A semi-structured questionnaire was administered by face-to-face interview method to collect data and the prevalence of frailty was assessed using Tilburg Frailty Indicator (TFI). Various sociodemographic factors related to frailty were also assessed and a p value of <0.05 was considered to be significant. Results: Among the 114 study participants 57(50%) were found to be frail. Factors like increasing age, female gender, presence of ≥2 chronic diseases, and lower socioeconomic class were significantly related to frailty in both univariate and multivariate regression analysis. Conclusions: Half of the study participants were found to be frail in the present study. The high prevalence of frailty among rural elderly populations emphasizes the need for targeted health interventions. The assessment of frailty using a simple tool like the TFI allows us to identify individuals who need more specialized and diversified care and thus supporting our elderly population in achieving healthy aging.